(untitled) (Indian Journal of Animal Production and Management, 2025)
A study was conducted in smallholder production systems to understand the feeding practices of dairy farmers in Meerut district. A total of 100 farmers having land holdings up to 4 acres were randomly selected, with 50 from rural and 50 from urban areas of the district. A suitable interview schedule was developed to collect observations. The study revealed major differences in rearing preferences among dairy farmers based on family structure and caste system in rural and urban areas. Most dairy farmers had considerable experience in dairy farming and reported a moderate income level. Significant differences were observed in the feeding of roughages and concentrates, formulation of concentrate, and the method of concentrate feeding across the two groups. However, improved feeding techniques such as urea treatment, feed and fodder conservation (as hay and silage), were not commonly adopted in either area. Major limitations faced by the farmers included infertility problems in animals, limited knowledge of technology-driven practices, and the unavailability of veterinary laboratory testing facilities.